“E o que é mais importante, está salvo o Brasil!”: perfil e atuação dos deputados da Assembleia Legislativa do RS no golpe civil-militar de 1964 - Catto, Guilherme (2017)
This Master Thesis was written at the Graduate Program in History (UFSM) and its main topic is the power relations and the support for the 1964 Civil-Military Coup from the Legislative Assembly of Rio Grande do Sul. Therefore, the research subject is the Legislature elected to State Parliament in 1962 – which was in its mandate in 1964 – and whose members we consider as Rio Grande do Sul political elite. We seek to analyze the political positioning by Assembly members regarding the political process experienced in Brazil in the 1960s; therefore, profiles of the parliamentarians were created, as well as a comparison between profiles of both groups: in opposition of the Coup and in support of the Coup. Therewith, we intend to show the profiles of the civilian supporters of the Coup, besides the profiles of the ones in opposition. In order to do this, two methodologies were used in different moments: prosopography, which was used to create the profiles of the parliamentarians, and sources, which were the parliamentarians‟ records, acquired at Memorial do Rio Grande do Sul, Correio do Povo and Zero Hora newspapers and the Brazilian Biographical-Historical Dictionary. Besides, content analysis was the methodology used for the examination of the political debate in the Assembly Annals.